2022
DOI: 10.1007/s00296-022-05153-w
|View full text |Cite
|
Sign up to set email alerts
|

Vasculitis flare after COVID-19: report of two cases in patients with preexistent controlled IgA vasculitis and review of the literature

Abstract: has been related to several autoimmune diseases, triggering the appearance of autoantibodies and endothelial dysfunction. Current evidence has drawn attention to vasculitis-like phenomena and leukocytoclastic vasculitis in some COVID-19 patients. Moreover, it has been hypothesized that COVID-19 could induce flares of preexisting autoimmune disorders. Here, we present two patients with previously controlled IgA vasculitis who developed a renal and cutaneous flare of vasculitis after mild COVID-19, one of them w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Renal involvement with biopsy-proven focally crescentic and segmentally necrotizing IgA nephropathy [ 20 ] or renal function deterioration requiring immunosuppressive therapy have been reported [ 21 ]. Interestingly, antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis has also been reported in subjects with previously controlled HSP after COVID-19 infection [ 22 ]. A review showed that COVID-19-associated HSP affects mostly adults, and the concomitant presence of other diseases led to a more severe course of vasculitis in older patients developing acute renal failure [ 23 ].…”
Section: Environment Microbial and Virus Infectionsmentioning
confidence: 99%
“…Renal involvement with biopsy-proven focally crescentic and segmentally necrotizing IgA nephropathy [ 20 ] or renal function deterioration requiring immunosuppressive therapy have been reported [ 21 ]. Interestingly, antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis has also been reported in subjects with previously controlled HSP after COVID-19 infection [ 22 ]. A review showed that COVID-19-associated HSP affects mostly adults, and the concomitant presence of other diseases led to a more severe course of vasculitis in older patients developing acute renal failure [ 23 ].…”
Section: Environment Microbial and Virus Infectionsmentioning
confidence: 99%
“…It should be pointed out that some studies support that SARS-CoV-2 has been linked to IgAV. The mechanisms involved in SARS-CoV-2 regulation of autoantibody generation, faulty development of Th2 response, endothelial inflammation and dysfunction, complement activation, NET production, and the upregulation of proinflammatory cytokines such as interleukin 6 may lead to vasculitis ( 125 127 ). The contradiction between the reduction in IgAV cases and the possible trigger may arise from the fact that SARS-CoV-2 may not be as strong a trigger as the other cold viruses or bacteria for IgAV.…”
Section: Pathogenesismentioning
confidence: 99%
“…All these patients received systemic CS. Biologics and immunosuppressants were administered only in 4 individuals due to concomitant renal impairment (1 rituximab, 2 mycophenolate mofetil, 1 cyclophosphamide), with a favorable response across published reports ( 28 ).…”
Section: Covid-19-associated Cutaneous Vasculitis/vasculopathymentioning
confidence: 99%